ANALISIS KEPUASAN DAN LOYALITAS KONSUMEN PRIMA FRESH MART (Pendekatan Service Quality) - Dini Amrilla Utomo; Rita Nurmalina (Forum Agribisnis, 2011)
Prima Fresh Mart (PFM) is one of retails in the form of specialty store in Indonesia, which provides a wide variety of chicken product. This study about analyze the relation between atributes and PFM’s service quality and the relation between service quality with PFM’s customer satisfaction and loyalty; and formulate the managerial implication to impove the PFM’s customer satisfaction and loyalty. This study utilized Structural Equation Model (SEM) analysis to evaluate how significant and strong the relation between the existing  variables. The result shows that tangible dimension is the most important variable that has the largest impact on customer satisfaction and loyality.PFM store’s atmosfer (X15) is the most important atribut to have the attention since it has the highest loading factor in tangible dimension. This means, X15 has the largest impact on customer satisfaction and loyalty. Products variance (X12) has the lowest loading factor since customer feels the products variance that PFM offers do not have much variance as other store offers. This caused X12 has the lowest impact on the customer satisfaction and loyality. On the other side, reliability dimension has the lowest loading factor which means the dimension needs to improve the atribut performance in order to increase the customer satisfaction.